Planning from within - Housing, land, and community-led development in Northern Remote Nibinamik First Nation: In conversation with Ila Beaver - McCartney, Shelagh (Canadian Planning and Policy / Aménagement et politique au Canada, 2026)
This special issue is enriched by the perspective of Ila Beaver, a community leader whose work bridges governance, wellness, and the lived realities of housing and infrastructure in Nibinamik First Nation. Raised in Summer Beaver and deeply rooted in Anishinaabe cultural life, Beaver brings a grounded understanding of how home, identity, and belonging are inseparable from land, language, and intergenerational connection. Her experience spans community leadership as Deputy Chief, mental wellness support across Matawa First Nations communities, employment and training initiatives, and long-term community comprehensive planning in Nibinamik First Nation — roles that together reveal how housing sits at the centre of community well-being and self-determination.Beaver's insights foreground the ways housing intersects with education, mental health, cultural continuity, and daily survival in remote northern communities. She speaks from the vantage point of someone who has lived overcrowding firsthand, led community-wide surveys to gather residents' priorities, and worked tirelessly to build a planning foundation that reflects Anishinaabe values rather than colonial policy. In her work, housing emerges not simply as shelter, but as a determinant of dignity, cultural belonging, and the capacity of Nibinamik to sustain and strengthen itself across generations.In preparing this piece, Beaver and Shelagh McCartney drew on over fifteen years of collaborative relationship to explore community-led planning, culturally grounded design, and long-term investment in local trades and governance capacity. Her voice is a powerful reminder that meaningful change begins from within — and that housing policy must follow the community's lead.